Treatment of defect pseudoarthroses with bone segment transport - Delimar, D; Klobucar, H; Jelić, M; Cicak, N; Korzinek, K (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2001)
PURPOSE OF THE STUDY: The most severe injuries during defense war in Croatia were caused by projectiles of high kinetic energy. Shell fragments bone they break the bone, transferring bone segments into additional individual projectiles. During this process periostal and endomedullary circulation is cut off reducing to a minimum the possibility of healing, leading to defects in long bone diaphyses. These are referred to as defect pseudoarthroses and are among the most difficult problems in reconstructive surgery of the musculo-articular system. This article presents bone segment transport as a method of choice for treating defect pseudoarthrosis. MATERIAL: During the defense Croatian war, in six-years period, 62 wounded persons were treated with Ilizarov method of bone segment transport. Among them, only one was female. Average age was 33 years. METHODS: The authors performed modified Ilizarov's method as standard procedure for bone segment transport in treatment of defect pseudoarthroses. After all soft tissues are held, corticotomy in metaphysis is performed and free bone segment transport started with Ilizarov method. Physical therapy provided adequate mechanical load, essential for bone healing and restoring the functionality of injured extremity. RESULTS: In the group of treated patients, the largest bridged defect was 20 cm, and the smallest one was only 1 cm. Infection arises in 20 of 60 patients. Contracture complications were ankle contractures, knee contractures and one elbow contracture. We also found one n. peroneus palsy and one limb amputation should be performed. DISCUSSION: Ilizarov method of bone segment transport presents the only procedure that could successfully and completely treat pseudarthroses, thus avoiding necessaries for limb amputations. Requirements in this procedure are experienced and highly qualified surgical team and high motivation and compliance of the patient.
Keywords: dospělí; Ilizarov Technique; Female; Pseudarthrosis; Adult; ženské pohlaví; Adolescent; vedení války; pseudoartróza; lidé; Leg Injuries; Arm Injuries; Middle Aged; Male; Ilizarovova technika; poranění paže; Warfare; lidé středního věku; mužské pohlaví; poranění dolní končetiny; mladiství; Humans